A novel rat model of gestational diabetes induced by intrauterine programming is associated with alterations in placental signaling and fetal overgrowth. (15th February 2016) - Capobianco, Evangelina; Fornes, Daiana; Linenberg, Ivana; Powell, Theresa L.; Jansson, Thomas; Jawerbaum, Alicia
Abstract: A family history of diabetes predisposes to gestational diabetes mellitus (GDM). We hypothesized that female offspring of rats with pre-gestational diabetes will develop GDM, a pathology associated with fetal overgrowth and altered placental signaling. We found normal glycemia and insulinemia in the offspring from pre-gestational diabetic rats at three months of age. However, consistent with GDM, maternal hyperglycemia and hyperinsulinemia and increased fetal weight were evident when compared to controls. In this intrauterine programmed GDM model, the placentas showed alterations in mTOR pathway: unchanged phosphorylation of 4EBP-1 and PKCα despite reduced total expression of 4EBP-1 and PKCα, and increased phosphorylation of SGK1. GDM placentas also showed reduced expression of PPARα and PPARγ, and increased lipoperoxidation, nitric oxide production and peroxynitrite-induced damage. We conclude that exposure of maternal diabetes in utero programs GDM in the female offspring, leading to a GDM model associated with impaired placental signaling pathways, increased pro-oxidant/pro-inflammatory environment and fetal overgrowth. Highlights: Experimental GDM can be induced by intrauterine programming. GDM rats show metabolic impairments and fetal overgrowth. GDM rats show impaired placental mTOR and PPAR pathways. Experimental GDM promotes placental oxidative and pro-inflammatory damage.